Figurações do Brasil: uma leitura das crônicas Humorísticas de Stanislaw Ponte Preta - Ribeiro, Francisco Cezar Rosa (2019)
The present study had as its aim to analyze the humour found in selected chronicles by Stanislaw Ponte Preta (1923-1968) as a means of representation of the Brazilian society, making recurring use of humorous, satirical and ironic resources. The research tried to establish the trajectory of this genre, from its beginning in Europe and evolution throughout the XIX and XX centuries in Brazil, leaving the page footer in the newspapers and assuming a permanent place in the Brazilian Literature. The theoretical support was based on the studies by Dimas (1976), Portela (1977), Meyer (1979), Diaféria (1984), Arrigucci (1987), Sá (1987), Candido (1992), Cardoso (1992), Bender; Laurito (1993), Resende (1995), Ribeiro (2001), Chaloub; Neves; Pereira (2005), Soares (2014), Damatta (1986), El Fahl (2003), Vasconcelos (2010), Soares (2014), among others.